Queer Presences and Absences - Taylor, Yvette. author. aut Link
XIII, 282 p.
Keywords: This book explores changes and continuations in lesbian, gay, bisexual, transgender and queer lives, identities and spatial practices in the 21st century from around the globe, using a range of methods to connect pasts, places and policies with contemporary times, linking individual and social presences (and absences) affectively and materially.